Refining the Paradigms of Early Recognition for Secondary Asthma [Letter] - Qi S; Wang Y; Zhang C (International Journal of General Medicine)
Shuai Qi,1,* Yi Wang,1,* Chong Zhang1,2 1School of Public Health, Gansu University of Chinese Medicine, Lanzhou, Gansu, People’s Republic of China; 2Department of Clinical Laboratory, Gansu Provincial Maternity and Child-Care Hospital, Lanzhou, Gansu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chong Zhang, Email zhch1972@163.com